Analisis Pengadaan Bahan Baku Serta Saluran Pemasaran Pada Usaha Kerupuk Bahagia Kota Bengkulu - Selvin Aristina; Yossie Yumiati; Rika Dwi Yuhartika (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
The cracker business is one form of agro-industry that plays an important role in supporting the community’s economy, especially in small and medium enterprises. The success of cracker business is strongly influenced by the availability of raw materials and the marketing system applied. The study aims to analyze the raw material procurement system and marketing channels of the Kerupuk Bahagia business in Bengkulu city. The research method used is descriptive with qualitative and quantitative approaches. The data consist of primary and secondary data. Primary data were obtained through observation and direct interviews with the business owner and retailers, while secondary data were obtained from literature, journals, and supporting document. The results show that raw material procurement is carried out through fixed suppliers with a scheduled purchasing system, ensuring stable availability and smooth production processes. The marketing channels consist of direct marketing from producers to consumers and indirect marketing through ratailers. The use of more that one marketing channel help expand market and increase sales volume.